Economic and social development of the world during the first decades of the 21st century - Bakirov, Vil Savbanovich; Kuklin, Volodymyr Michailovich; Sirenka, Anna Valierievna (Generis Publishing, 2022)
This book discusses the impact of a developed economy and democracy on the social life of the peoples of the world during the liberal reforms of the first decades in the context of the liberalization of economic and social life in the 21st century. It is shown that it was the liberalization of economic life that gave a significant impetus to the development of civilization, especially with the positive impact of informatization and globalization on business relations. It is noted that it was the concentration of capital and the growth in the number of owners of production assets that contributed to the economic success of many countries.
Размещены оглавление и введение книги, издательство ее планирует продавать, поэтому размещен не весь текст
Keywords: wealth; democracy; liberalization of the economy; growth in the number of owners of productive assets